Painter and His Double in the Artistic Opus of Katarina Radojlović) - Марковић, Срђан; Милићевић, Небојша (Poznańskie Studia Slawistyczne, 2017)
The painting of Katarina Radojlovic1 , gone too soon as it happens too often in life, carries inherently and by its nature the autobiographical features that do not allow factual interpretations and anecdotal storytelling. Furthermore, the painter’s need to touch the “impersonal” without losing her own identity, however paradoxical it may sound, makes difficult any attempt to classify or rank her artistic opus within the existing courses of the contemporary Serbian art scene. After all, what’s the point of classification since during the process of creating the author was crystal clear about her painting being first and foremost cosa mentale. It is actually a form of searching for her, dealing with loneliness and meaningless in an effort to rediscover the meaning of reality via work of art that will by its own standards seek to establish a relationship between form and function of visual expression. This effort, we would say, is quite clearly to be identified in the last cycles of her artistic opus: Theatre of Shadows, Moonlight Stories and Imprint of a Shadow.